Consultations with health care providers and use of self-management strategies for prevention and treatment of COVID-19 related symptoms. A population based cross-sectional study in Norway, Sweden and the Netherlands. (March 2022) - Kristoffersen, Agnete E.; van der Werf, Esther T.; Stub, Trine; Musial, Frauke; Wider, Barbara; Jong, Miek C.; Wode, Kathrin; Danell, Jenny-Ann B.; Busch, Martine; Hoenders, H.J. Rogier; Nordberg, Johanna H.
Abstract: Objectives: The present study was initiated to determine consultations with health care providers and use of self-management strategies for prevention or treatment of COVID-19 related symptoms in countries with a full lockdown (Norway), a partial lockdown (the Netherlands) and no lockdown (Sweden) during the first three months of the COVID-19 pandemic, and if such use correlates with worries of being infected by COVID-19 disease. Design: Data were collected in collaboration with Ipsos A/S in April-June 2020. An adapted version of the International Questionnaire to measure use of Complementary and Alternative Medicine (I-CAM-Q) was used with the categories "for prevention of COVID-19" and "to treat COVID-19-related symptoms" added. Data were collected among a representative sample in Norway, Sweden and the Netherlands using data assisted telephone interviews (Norway, n=990 and Sweden, n=500), and an online survey (the Netherlands, n=1004). Total response rate was 30%. Results: Very few consulted a health care provider with the intention to treat or prevent COVID-19 (1.2% and 1.0% respectively) with medical doctors mostly visited (1.0% and 0.9% respectively). Similarly, the use of self-management strategies to prevent or treat COVID-19 was low (3.4% and 0.2% respectively); most commonly used for prevention of COVID-19 were vitamins and minerals (2.8%). Consultations with health care providers and use of self-management strategies for prevention of COVID-19 were positively associated with worries of being infected with COVID-19. Conclusions: The COVID-19 pandemic does not seem to have evoked a large-scale difference in behavior related to consultations with health care providers or the use of self-management strategies in any of the three countries. Highlights: COVID-19 has changed the complementary therapies (CT) people use. A small increase in CT use was found in the first wave of the COVID-19 pandemic. Few used complementary therapies for prevention and treatment of COVID-19. Prevention of COVID-19 was positively associated with worries of being infected.